Partial-update adaptive filters and adaptive signal processing : design analysis and implementation - Dogancay, Kutluyl (Elsevier Academic Press, 2008)
Partial-update adaptive signal processing algorithms not only permit significant complexity reduction in adaptive filter implementations, but can also improve adaptive filter performance in telecommunications applications. This book gives state-of-the-art methods for the design and development of partial-update adaptive signal processing algorithms for use in systems development. Partial-Update Adaptive Signal Processing provides a comprehensive coverage of key partial updating schemes, giving detailed information on the theory and applications of acoustic and network echo cancellation, channel equalization and multiuser detection. It also examines convergence and stability issues for partial update algorithms, providing detailed complexity analysis and a unifying treatment of partial-update techniques. Features: . Advanced analysis and design tools . Application examples illustrating the use of partial-update adaptive signal processing . MATLAB codes for developed algorithms This unique reference will be of interest to signal processing and communications engineers, researchers, R & D engineers and graduate students. "This is a very systematic and methodical treatment of an adaptive signal processing topic, of particular significance in power limited applications such as in wireless communication systems and smart ad hoc sensor networks. I am very happy to have this book on my shelf, not to gather dust, but to be consulted and used in my own research and teaching activities"--Professor A.G. Constantinides, Imperial College, London About the author: Kutluyil Doganay is an associate professor of Electrical Engineering at the University of South Australia. His research interests span statistical and adaptive signal processing and he serves as a consultant to defence and private industry. He was the Signal Processing and Communications Program Chair of IDC Conference 2007, and is currently chair of the IEEE South Australia Communications and Signal Processing Chapter. * Advanced analysis and design tools * Algorithm summaries in tabular format * Case studies illustrate the application of partial update adaptive signal processing * MATLAB code listings on an accompanying website.